Was COVID-19 a game changer for the Tokyo and Beijing Olympics? - Liu, X.; Ornelas, E.; Shi, H. (Journal of Sports Economics, 2024)
No, it was not. We do not find evidence that the COVID-19 pandemic affected the distribution of medals in a systematic way. Countries that suffered a higher share of deaths due to the pandemic, or that imposed stricter lockdowns, performed just as prior performances and standard economic and demographic variables alone would have predicted. Hence, while COVID-19 has surely affected the performance of some individual athletes, it did not have a perceptible effect on the distribution of medals across countries. The only impact of the pandemic on the outcome of the Games was to reduce the advantage that host countries traditionally have. This effect, probably caused by the lack of local spectators in most competitions, was particularly strong for teams` events, where the "host effect" vanished.